Rhetorical Exercises as a Means of Forming Future Primary School Teachers’ Communicative Competence (Linguostylistic Studies, 2017)
The process of preparing future teachers for speech activity involves the formation of their communicative skills, which are the part of their identity and are important not only for successful professional activity, but also for participation in various spheres of life in the society. The article determines the role and place of rhetorical exercises and tasks in the process of developing communicative competence of primary school teachers. The author has worked out the system of exercises and tasks promoting the acquisition of basic knowledge in rhetoric and the formation of professionally important linguistic and rhetorical skills of the students-bachelors specialising in primary education. The practical classes in Basics of Rhetoric in Primary School facilitate development of the following students’ communicative skills: to conduct a monologue on professional topics; to conduct an effective, constructive conversation on any topic, using verbal and non-verbal means; to acquire the skills of the polemic art, to have background knowledge of ethical culture of constructive dialogue and polylogue (debate, polemics, discussion).
Keywords: rhetoric; rhetorical exercises and tasks; rhetorical skills; communicative competence; primary school teachers